2014
DOI: 10.1126/science.1251652
|View full text |Cite
|
Sign up to set email alerts
|

The Resolution Revolution

Abstract: Advances in detector technology and image processing are yielding high-resolution electron cryo-microscopy structures of biomolecules. [Also see Report by Amunts et al. ]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
671
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,101 publications
(705 citation statements)
references
References 10 publications
2
671
0
9
Order By: Relevance
“…Although good studies with beautiful TEM can be found where cryo‐electron microscopy47 and 3D methods such as cryo‐electron tomography19, 48 and 2D49 and 3D single‐particle analyses50 have been put to use on soft matter structures, too many misapplications and misinterpretations are present in the current literature.…”
Section: Quality and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Although good studies with beautiful TEM can be found where cryo‐electron microscopy47 and 3D methods such as cryo‐electron tomography19, 48 and 2D49 and 3D single‐particle analyses50 have been put to use on soft matter structures, too many misapplications and misinterpretations are present in the current literature.…”
Section: Quality and Outlookmentioning
confidence: 99%
“…Other research fields that use cryo‐TEM are making more and more use of new technical developments such as the volta‐phase plate56 that enhances image contrast and allows imaging in focus. Another great and recent development is the direct detection camera57 that induced a true resolution revolution47 in the field of structural biology because of its ability to record movies that allow the correction for drift and the detection of radiation damage that accumulates with exposure time.…”
Section: Quality and Outlookmentioning
confidence: 99%
“…The wide application of direct electron detection device (DDD) cameras enabled a 'resolution revolution' in singleparticle cryo-EM [10]. All DDD cameras have significantly higher DQEs than photographic film and scintillator-based cameras [4,5,11].…”
Section: Image Acquisition Using Direct Electron Detection Camerasmentioning
confidence: 99%
“…This makes it very difficult to be purified in abundant and homogenous form, to be crystallized, therefore to be solved structurally using X-ray crystallography. The most recent technique revolution in cryo-electron microscopy made it possible to solve macromolecules at atomic resolution without the crystallization step [4]. The even more powerful capability of the new technology is to separate compositional or conformational heterogeneous molecule structures by computation after taking images of them in frozenhydrated specimen in an electron microscope.…”
mentioning
confidence: 99%